National Policy on Libraries at a Time of Convergence: The UK Experience. Issue 3 (1st December 2014) - Stephens, Andy
<x xml:space="preserve">Abstract</x> The United Kingdom does not have a formal overarching national information and library policy. Nevertheless there may be some interest in what we do as a country which does not have such a policy – and the role of the national library in this – particularly at a time of digital/analogue convergence. The presentation will start by describing the landscape of library provision in the UK and its governance, funding and policy framework. It will then go on to review recent developments at regulatory, policy and practical levels. These include: developments in open access (including the Access to Research initiative), reviews of the future of public libraries including e-lending, and the national role of the British Library in, for example, e-legal deposit, the national roll-out of Business and IP centres, and in providing national underpinning for a national distributed collection.